Mekanisme Penyebaran Cacar Monyet dan Faktor-Faktor Yang Mempengaruhinya - I Ketut Suarayasa; Zulkifli; Ofel mazmur Kristoper (Yayasan Literasi Sains Indonesia, 2023)
Introduction: On May 29, 2022, the World Health Organization (WHO) described the global public health risk from multi-country monkeypox outbreaks in non-endemic countries as